Android-Based Business Bookkeeping Training to Improve Financial Management of Micro, Small and Medium Enterprises (MSMEs) in Cilibende, Babakan Village, Bogor - Ratih Pratiwi; Asty Khairi Inayah Syahwani; Resti Jayeng Ramadhanti; Novi Rosyanti (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
MSMEs are one form of contribution that can affect economic growth in a region. MSME actors need to maintain and develop their business to a larger business scale. One of the factors in supporting the creation of progress in MSMEs is the functioning of the recording and bookkeeping system in these business fields. Based on a survey conducted on MSME actors in Babakan Village in Bogor City, 4 out of 17 MSME actors did financial records manually in a diary, but it was not in accordance with accounting standards, so business actors did not know for sure the profits and losses they received. This community service carried out for MSME actors includes basic training in daily financial recording and digital bookkeeping using the Buku Warung application, located in Babakan Village, Bogor City. The purpose of this training is to improve understanding of accounting and finance as well as facilitate business actors (MSMEs) in recording transactions and bookkeeping to support business activities. The training begins with the presentation of the material, practice in using the Warung Buku application. The results that can be achieved after the training are that all MSME actors in Babakan Village, Bogor City can record and report their business activities through the Warung Buku application..